Comparison of the Electrophilic Reactivities of N‐Acylpyridinium Ions and Other Acylating Agents1. Issue 11 (20th February 2013) - Nigst, Tobias A.; Mayr, Herbert
Abstract: The kinetics of the reactions of carbanions, carboxylate anions, and primary and secondary amines with acylating agents were studied in acetonitrile and dimethyl sulfoxide (DMSO) under first‐order conditions by UV/Vis spectrophotometry and conductimetry. Whereas reactions of a large variety of nucleophiles with ordinary carbanions and Michael acceptors generally follow the linear free energy relationship lg k 2 (20 °C) = s N ( N + E ), separate correlation lines for different types of nucleophiles were found when (lg k 2 )/ s N was plotted against N for the reactions with acyl derivatives2 –5 . Even when nucleophilic attack is rate determining, the reactivities of acylating agents towards nucleophiles cannot be described by a single set of nucleophile‐independent electrophilicity parameters. Abstract : The kinetics of the reactions of amines and carbanions with acylating agents were studied in acetonitrile and DMSO solution at 20 °C. Separate correlation lines for different types of nucleophiles were found when (lg k 2 )/ s N was plotted against the nucleophilicity parameters N for these reactions, indicating the limitation of the depicted correlation.